IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 19 TAHUN 2016 TENTANG PEDOMAN PENGELOLAAN BARANG MILIK DAERAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH PROVINSI LAMPUNG (Studi Tentang Penghapusan Peralatan dan Mesin) - Abbas Abbas; Agus Purnomo; Merliyana Merliyana (e-JKPP, 2020)
Empirically, the implementation of the Regulation of the Minister of Home Affairs Number 19 Year 20116 concerning Guidelines for the Management of Regional Property (Equipment and Machinery Abolition), in Lampung Province has not been effective, this has allowed employee performance to decline. The purpose of this paper is to determine the procedure for eliminating Regional Property in the form of equipment and machines and to determine the supporting factors and constraints that occur in the procedure for deleting Regional Property in the form of equipment and machines.This research method is to use a qualitative research type with descriptive analysis method, the data collection technique used by the author in making this report is to use the observation method, direct interviews with BPKAD officials in Lampung Province, besides that the author also conducts documentation studies and literature studies to support compliance. this research.The results of this study are to find out about the procedures for the elimination of regional property in the form of equipment and machines and to find out what are the supporting factors, the causes of the constraints that become obstacles in the procedure for removing equipment and machines. vehicles based on Permendagri Number 19 of 2016 at BPKAD Lampung Province. In this study, through interviews with BPKAD assets in Lampung Province, the author can find out that the procedure for deleting Regional Property in the form of equipment and machines shows that the overall procedure carried out by the Lampung Province BPKAD has been effective and is in accordance with Permendagri Number 19 of 2016 but there are still obstacles. because the recording, inspection and security were less than optimal which led to changes in the presentation of asset values on the balance sheet.